(untitled) (REMUNOM, 2024)
his article deals with cases of fraud in payroll loans, especially when involving elderly people, in order to analyze and evaluate the rights and vulnerability of this group of people, answering what are the legal consequences in cases of proof of fraud. The objective of this article, therefore, is, through bibliographical and documentary research, to explain the vulnerability of the elderly in relation to consumer relations and, also, to address whether or not there is responsibility on the part of financial institutions in cases where fraud has been proven.